Beautiful you - Palahniuk, Chuck; Monda, Carol; Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2014)
Invited by notorious playboy C. Linus Maxwell to a Paris hotel, Manhattan legal associate Penny Harrigan discovers that she is a test subject for the final development of sex toys for women that will render men obsolete and make Maxwell the most powerful person in the world.
Title from container.
Compact disc.
In container (17 cm.).
"With tracks every 3 minutes for easy book marking"--Container.
Narrated by Carol Monda.
Keywords: Women lawyers -- Fiction; Sex toys -- Fiction; Erotic fiction; Humorous fiction; Suspense fiction; Audiobooks